Quantitative single‐molecule imaging of TNFR1 reveals zafirlukast as antagonist of TNFR1 clustering and TNFα‐induced NF‐ĸB signaling. Issue 2 (13th May 2020) - Weinelt, Nadine; Karathanasis, Christos; Smith, Sonja; Medler, Juliane; Malkusch, Sebastian; Fulda, Simone; Wajant, Harald; Heilemann, Mike; van Wijk, Sjoerd J. L.
Abstract: TNFR1 is a crucial regulator of NF‐ĸB‐mediated proinflammatory cell survival responses and programmed cell death (PCD). Deregulation of TNFα‐ and TNFR1‐controlled NF‐ĸB signaling underlies major diseases, like cancer, inflammation, and autoimmune diseases. Therefore, although being routinely used, antagonists of TNFα might also affect TNFR2‐mediated processes, so that alternative approaches to directly antagonize TNFR1 are beneficial. Here, we apply quantitative single‐molecule localization microscopy (SMLM) of TNFR1 in physiologic cellular settings to validate and characterize TNFR1 inhibitory substances, exemplified by the recently described TNFR1 antagonist zafirlukast. Treatment of TNFR1‐mEos2 reconstituted TNFR1/2 knockout mouse embryonic fibroblasts (MEFs) with zafirlukast inhibited both ligand‐independent preligand assembly domain (PLAD)‐mediated TNFR1 dimerization as well as TNFα‐induced TNFR1 oligomerization. In addition, zafirlukast‐mediated inhibition of TNFR1 clustering was accompanied by deregulation of acute and prolonged NF‐ĸB signaling in reconstituted TNFR1‐mEos2 MEFs and human cervical carcinoma cells. These findings reveal the necessity of PLAD‐mediated, ligand‐independent TNFR1 dimerization for NF‐ĸB activation, highlight the PLAD as central regulator of TNFα‐induced TNFR1 oligomerization, and demonstrate that TNFR1‐mEos2 MEFs can be used to investigate TNFR1‐antagonizing compounds employing single‐molecule quantification and functional NF‐ĸB assays at physiologic conditions. Graphical Abstract: Validates and characterizes membrane TNFR1 clustering antagonists using quantitative super‐resolution microscopy with single‐molecule resolution at physiological levels.